Numerical and experimental investigation for swing-up control of an inverted pendulum using Arduino microcontroller - Donatoni, M. M. [UNESP]; Chavarette, F. R. [UNESP]; Preto, E.; Karmouche, D. C. J. [UNESP] (Univ Malaysia Pahang, 2024)
The Inverted Pendulum is a classic control problem, it has non-linear dynamics, is underactuated and is naturally unstable. Thus, developing a system capable of controlling it goes through challenges such as modeling, design requirements, and implementation of the control hardware. This work proposes the swing -up of the linear inverted pendulum using the energy method with adjustable parameters, followed by a linear quadratic regulator controller stabilization. This work demonstrates how the system can be implemented using an Arduino microcontroller to acquire state variables and control commands. Furthermore, as a highlight, the implemented algorithm indicates a way to stabilize the sampling frequency, making the derivative process stable in the applied hardware and optimizing the control. The applied method was efficient in performing the swing -up, consistent with the simulations, and as effective as seen in the literature.
Keywords: Inverted Pendulum; Swing-up; Energy-based; LQR; Microcontroller; Arduino